2006
DOI: 10.1152/ajplung.00389.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides induce IL-6 release from human airway epithelia via P2Y2and p38 MAPK-dependent pathways

Abstract: Extracellular nucleotides can mediate a variety of cellular functions via interactions with purinergic receptors. We previously showed that mechanical ventilation (MV) induces airway IL-6 and ATP release, modifies luminal nucleotide composition, and alters lung purinoceptor expression. Here we hypothesize that extracellular nucleotides induce secretion of IL-6 by small airway epithelial cells (SAEC). Human SAEC were stimulated with nucleotides in the presence or absence of inhibitors. Supernatants were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 79 publications
(85 reference statements)
8
51
0
Order By: Relevance
“…We have to note that our previous works did not exclude a function of P2Y 2 in LPS-induced IL-8 secretion [14,15]. Other previous studies showed that the activation of this receptor was coupled to MCP-1 release from rat alveolar and peritoneal macrophages [22] and IL-6 release from human airway epithelia [32].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have to note that our previous works did not exclude a function of P2Y 2 in LPS-induced IL-8 secretion [14,15]. Other previous studies showed that the activation of this receptor was coupled to MCP-1 release from rat alveolar and peritoneal macrophages [22] and IL-6 release from human airway epithelia [32].…”
Section: Discussionmentioning
confidence: 81%
“…We have to note that our previous works did not exclude a function of P2Y 2 in LPS-induced IL-8 secretion [14,15]. Other previous studies showed that the activation of this receptor was coupled to MCP-1 release from rat alveolar and peritoneal macrophages [22] and IL-6 release from human airway epithelia [32].Altogether, the results reported in this paper suggest that the P2Y 2 and P2Y 6 receptors may play an important role in the innate immune response resulting from TLR2 activation. As IL-8 secreted by a variety of inflammatory cells including monocytes has been implicated in a number of inflammatory/infectious diseases, such as rheumatoid arthritis [33], inflammatory bowel disease [34], psoriasis [35,36], palmoplantar pustulosis [37,38], asthma and chronic obstructive pulmonary disease [39], targeting P2Y 2 and/or P2Y 6 receptors may reveal as novel therapeutic approaches to fight these diseases.…”
mentioning
confidence: 80%
“…However, previous in vitro studies have revealed that supernatants from hypoxia-or stretch induced injury contained adenosine that diminished endothelial leakage (14,43). Additional studies in vivo demonstrated prominent increases in pulmonary adenosine levels with mechanical ventilation (13,14). The increased adenosine level was associated with the enhanced expression of ectoapyrase (CD39) and ecto-5′-nucleotidase (CD73) that hydrolyze ATP to adenosine at the cell surface of neutrophils and endothelial cells (43).…”
Section: Discussionmentioning
confidence: 98%
“…A couple of recent studies have demonstrated that mechanical ventilation in rats and mice increases the level of pulmonary adenosine (13,14), and that mice deficient for extracellular adenosine generation show increased pulmonary edema and inflammation after VILI (14). Once in the extracellular milieu, adenosine exerts its biological effects through binding to the G-protein coupled adenosine receptors including A 1 R, A 2A R, A 2B R, and A 3 R (8,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the P2Y 2 R promotes inhibition of Na + absorption as well as CFTR-dependent and CFTRindependent Cl − secretion, ciliary beating, and mucin secretion [6,7]. In addition, nucleotides within the airway surface liquid (ASL) are potent pro-inflammatory signaling molecules acting on purinergic receptors expressed on immune/ inflammatory cells or by promoting the release of cytokines and other chemoattractants from lung epithelial cells [8][9][10][11]. Thus, the rates of nucleotide release and metabolism in healthy airways are finely regulated to maintain effective MCC without promoting airway inflammation.…”
Section: Introductionmentioning
confidence: 99%